2020
DOI: 10.1371/journal.pone.0240577
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel multiepitope constructs-based peptide vaccine against the structural S, N and M proteins of human COVID-19 using immunoinformatics analysis

Abstract: The causative agent of severe acute respiratory syndrome (SARS) reported by the Chinese Center for Disease Control (China CDC) has been identified as a novel Betacoronavirus (SARS-CoV-2). A computational approach was adopted to identify multiepitope vaccine candidates against SARS-CoV-2 based on S, N and M proteins being able to elicit both humoral and cellular immune responses. In this study, the sequence of the virus was obtained from NCBI database and analyzed with in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 50 publications
(129 reference statements)
0
30
1
Order By: Relevance
“…It is important to take into account AMP development programs that are used to predict a possible immune response and allergic reactions to a specific peptide structure [ 238 ]. This validation is especially important for drug development based on AMPs, in particular, antiviral drugs, which will be discussed in more detail in the final section of this review.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to take into account AMP development programs that are used to predict a possible immune response and allergic reactions to a specific peptide structure [ 238 ]. This validation is especially important for drug development based on AMPs, in particular, antiviral drugs, which will be discussed in more detail in the final section of this review.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…High-performance in silico technologies currently allows the development of new approaches to the creation of peptide vaccines. Antigenic epitopes found in viral proteins can simultaneously meet several criteria, including immunodominant regions, non-allergenicity, population coverage, and lack of variability (conservatism) for efficient binding and molecular interaction with HLA (human leukocyte antigen) and TLR (toll-like receptor) alleles [ 238 ]. To evaluate the effectiveness of peptide vaccines against SARS-CoV-2, the frequencies of the HLA haplotypes can be used to predict the coverage of the developed vaccine.…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…In studies conducted by Kar et al [ 78 ], Dar et al [ 79 ], and Kumar et al [ 80 ], S protein alone was used as a target for epitope prediction. However, in other pieces of research conducted by Kalita et al [ 81 ] and Khairkhah et al [ 82 ], S, M, and N protein were identified as target antigens. Furthermore, S, E, and N proteins were reported as target antigens by Kumar et al [ 83 ] .…”
Section: Discussionmentioning
confidence: 96%
“…According to the prediction of the transmembrane helix topology in a three-dimensional (3-D) model [ 22 ], the N- and C-terminal portions of the membrane glycoprotein were exposed outside and inside the particle of SARS-CoV-2, respectively. Both B-cell and T-cell epitopes within a highly conserved region of membrane protein have been revealed [ 23 , 24 ]. Results from a recent study demonstrated that membrane glycoprotein inhibited the type I and III interferon production by targeting the signaling mediated by retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA-5) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%